2015
DOI: 10.1007/s11165-015-9460-3
|View full text |Cite
|
Sign up to set email alerts
|

From Geocentrism to Allocentrism: Teaching the Phases of the Moon in a Digital Full-Dome Planetarium

Abstract: An increasing number of planetariums worldwide are turning digital, using ultrafast computers, powerful graphic cards, and high-resolution video projectors to create highly realistic astronomical imagery in real time. This modern technology makes it so that the audience can observe astronomical phenomena from a geocentric as well as an allocentric perspective (the view from space). While the dome creates a sense of immersion, the digital planetarium introduces a new way to teach astronomy, especially for topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
1
21
0
4
Order By: Relevance
“…• A unit of work on six astronomical concepts that spanned several weeks and included learning activities such as internet-based research, observations of the moon, and the use of a three-dimensional computer model (Barnett & Morran, 2002); • An excursion to a planetarium (Chastenay, 2016;Stover & Saunders, 2000);…”
Section: Conceptual Change Instructional Approaches and Methods Emplomentioning
confidence: 99%
See 2 more Smart Citations
“…• A unit of work on six astronomical concepts that spanned several weeks and included learning activities such as internet-based research, observations of the moon, and the use of a three-dimensional computer model (Barnett & Morran, 2002); • An excursion to a planetarium (Chastenay, 2016;Stover & Saunders, 2000);…”
Section: Conceptual Change Instructional Approaches and Methods Emplomentioning
confidence: 99%
“…As well, recent issues of particularly relevant journals were searched manually throughout the preparation of the review to ensure data collection was thorough, namely the Finally, the reference lists of relevant studies were analyzed to identify any further relevant studies, and so on, until a point of saturation was reached where the first author was certain that no more relevant studies could be obtained from this process. Particular attention was given to three existing literature reviews in this process (Cheek, 2010;Francek, 2013;Lelliott & Rollnick, 2010).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu (2005) has highlighted the potential benefits of fulldome for astronomy education: revealing three-dimensional (3D) spatial relationships, demonstrating accurate motions and lighting of astronomical bodies, and placing the viewer in multiple frames of reference. Studies in discipline-based astronomy education research has typically shown how fulldome theaters benefit topics that involve understanding of spatial relationships, such as motions of celestial bodies (Plummer, Kocareli, & Slagle, 2014), phases of the Moon (Chastenay, 2015), and Earth's seasons (Yu, Sahami, Sahami, & Sessions, 2015). Yet there are other aspects of the fulldome theater experience that have not been well studied in prior research.…”
mentioning
confidence: 99%
“…On the final day of the 4-day planetarium program, students were given a list of 7 planetarium instructional features and asked to rank in order from most important (1) to least important (7), "What about the planetarium has helped you in thinking about or understanding astronomical concepts?" The top seven list was compiled by the researcher, the planetarium director, and were items mentioned in planetarium research as being important aspects of this type of informal science institution (ISI) -immersive environment, dynamic modeling, and scale (Littmann, 2009); immersive environment (Yu, Sahami, Sahami & Sessions, 2015); offering different perspectives (Chastenay, 2015); and motion (dynamic modeling) and scale (Plummer, 2014b(Plummer, , 2014c.…”
Section: Top 7 Ranking Listmentioning
confidence: 99%